(untitled) (Medical Forum Monthly, 2021)
Objective: This study was conducted to evaluate the correlation of width of the maxillary anterior teeth with the length of index, middle and ring fingers. Study Design: Cross-Sectional Study Place and Duration of Study: This study was conducted at the Department of Prosthodontics, Institute of Dentistry, Liaquat University of Medical and Health Sciences, Jamshoro from June 2019 to December 2020. Materials and Methods: Maxillary casts were made from alginate impressions. An adaptable ruler was used to calculate the Inter-Canine Distance (ICD). The length of the patients' index, middle, and ring fingers was then measured with a vernier caliper with a precision of 0.01 mm from the tip of the finger to the lower border line of the fingers. Data was analyzed using SPSS version 17. Pearson's correlation coefficient was applied to find out the correlation among length of index, middle and ring finger with ICD. Results: One hundred twenty volunteers participated in this study. The mean age was 24.30±3.304. The sample consisted of 66% males and 34 females. Descriptive statistics of the length of Index finger showed mean score 74.35±3.400, length of Middle finger showed mean score 82.22±3.417, length of Ring finger showed mean score 78.42±3.400, the ICD showed mean score 50.06±2.394. The correlation between length of Index, Middle and Ring fingers and ICD was positive and statistically significant (P-Value= 0.001). Conclusion: It is concluded that there was significant correlation between the ICD and length of index, middle and ring fingers.